Stable emulsion (SE) alone is an effective adjuvant for a recombinant, baculovirus-expressed H5 influenza vaccine in healthy adults: A Phase 2 trial. Issue 6 (7th February 2017) - Treanor, John J.; Chu, Laurence; Essink, Brandon; Muse, Derek; El Sahly, Hana M.; Izikson, Ruvim; Goldenthal, Karen L.; Patriarca, Peter; Dunkle, Lisa M.
Abstract: Background: Influenza A viruses of the H5 subtype have been identified as important targets for development of vaccines. Achievement of potentially protective antibody responses against pandemic strains has usually required the use of adjuvants. Objectives: We evaluated a candidate A/Indonesia/05/2005 (H5) vaccine generated by baculovirus expression of recombinant hemagglutinin (HA) protein with or without stable emulsion (SE) as an adjuvant. Methods: Healthy subjects 18–49 years old were randomized (1:1:1:1) to receive two doses of rHA at 7.5 ug per dose (no adjuvant), or 3.8 ug, 7.5 ug, or 15 ug per dose formulated with 2% SE separated by 21 days, and serum from day 0, 21, 42, and 201 assessed by hemagglutination-inhibition. Results: 341 subjects were enrolled in the study and 321 received two doses of vaccine. Vaccination was well tolerated in all groups. After two doses, seroconversion was noted in only 9% (95% confidence interval 4%, 17%) of recipients of unadjuvanted vaccine at 7.5 ug, but in 70% (59%, 80%), 76% (65%, 85%), and 83% (73%, 91%) of those receiving adjuvanted vaccine at 3.8 ug, 7.5 ug, or 15 ug respectively. Conclusions: Stable emulsion alone is an effective adjuvant for rH5 vaccine in healthy adults. All three adjuvanted dose groups met the current criterion for seroconversion rate for pandemic vaccines. This dose-ranging study also identified a group (15 ug per dose formulated with 2% SE) that met the criteria for both seroconversion and percentage of subjects achieving an HI antibody titer ⩾ 40. These Phase 2 data support the further clinical development of SE adjuvanted Panblok H5. Clinical trial registration:NCT01612000 . The protocol was approved by the relevant Institutional Review Board for each study site, and the study was conducted in accordance with the Declaration of Helsinki, International Conference of Harmonisation – Good Clinical Practice, and all applicable laws and regulations. All participants provided written informed consent before study procedures.